Reliable predictors of reduced redundancy test performance: The interaction between lexical bonds and test takers' depth and breadth of vocabulary knowledge. (January 2018) - Janebi Enayat, Mostafa; Babaii, Esmat
The present study intended to investigate whether test takers' breadth and depth of vocabulary knowledge can contribute to their efficient use of lexical bonds while restoring damaged texts in reduced redundancy tests. Moreover, the moderating role of general language proficiency was investigated in this interaction. In so doing, Vocabulary Levels Test (VLT), Word Associates Test (WAT), and a series of C-tests with high and low lexical bonds were administered to two groups of 85 upper-intermediate and 50 lower-intermediate EFL learners. Results of multiple regression analyses indicated the following: (a) breadth and depth of vocabulary knowledge played dissimilar roles for test takers with different levels of language proficiency; (b) depth of vocabulary knowledge was a better predictor for high-bond texts; and (c) test takers with higher levels of language proficiency made more efficient use of lexical bonds as contextual cues. The findings point to the necessity of improving learners' depth of vocabulary knowledge, especially at lower levels of language proficiency where vocabulary knowledge is mostly a matter of size rather than quality.